Guild composition and habitat use of voles in two forest landscapes in south-eastern Norway. - GORINI, LUCREZIA; BOITANI, Luigi; Linnel, John D. C.; Hauptmann, Ulrike; Odden, Morten; Wegge, Per; Nilsen, Erlend B. (Integrative Zoology, 2011)
It is widely believed that intensive forestry has influenced small mammal population dynamics, and thereby the entire mammalian community in Fennoscandian boreal forests. The nature of these impacts on the different species is subject to debate. We live-trapped voles between 2006 and 2009 in 2 commercially harvested forests in south-eastern Norway. We investigated the variation in vole abundance among habitat types (e.g. mature forest and clear-cut) and the hypothesis that graminivorous species such as field voles (Microtus agrestis L.) benefit from clear-cuts at the expense of forest dwellers (i.e. the bank vole, Myodes glareolus Schreb.), using fine-scale descriptors of the ground vegetation. We could not find support for the hypothesis that field voles show a preference for clear-cuts, and their overall abundance was low, while bank voles were the dominant species in all habitat types, including clear-cuts in the peak and pre-peak years. We found a positive association between bank vole abundance and bilberry (Vaccinium myrtillus L.) availability rather than a specific habitat type. Low field vole density in clear-cuts might be due to variation in local productivity and ground vegetation as well as to large variation in the species temporal dynamics. The latter is particularly associated with the widespread decline of field voles in Scandinavia. Logging has the potential to negatively affect bank vole population dynamics because of the negative effect on bilberry development.